Willingness of employers to support disability management in the workplace from SOCSO’s perspective - Pannirselvam, Rajamanikam (2015)
In the current competitive edge, many healthy workers who become disable due to injuries, accidents, chronic illness or birth defect has been continued to be the poorest, less educated and least hired which was contributed by several barriers that stop them from participating in the labour market. The common barrier is the employer’s perception toward hiring the disable people in their workplace and this is the biggest constraint for the disable people to mingle in the workgroups in the society. This survey based research study was conducted basically to analyse the influence characteristics of employers in employing disable people in their workplace and for this purpose, the study was mainly targeted number of employers from Klang valley, Malaysia. Precisely, the connection between gender and total employees in an organization was identified by analysing the total number of employees in the organization, familiarity with disability workers and prior work experience with disability people together with elements of understanding and beliefs towards disability was explored. Results from this study indicate that employers’ attitudes are generally positive and the common barriers also have been identified. Overall familiarity with disability, size of organizations and gender can be predictable characters in determining the employer’s attitude in employing people with disabilities. This study also indicates that employers are willing to support disability management in the workplace. Furthermore, constraints in conducting this study together with future recommendations for other researchers are provided in this study